Skeletal prognathism with factor XII deficiency causing complications in perioperative management: A case report - Hayato Hamada; Yoko Kawase-Koga; On Hasegawa; Masato Watanabe; Daichi Chikazu (Elsevier, 2021)
A 21-year-old man with mandibular prognathism was referred to Tokyo Medical University Hospital. The patient was diagnosed as having skeletal prognathism. Preoperative laboratory routine tests were performed, and the patient was found to have factor XII deficiency. On the night 2 days after osteotomy, the patient was found to have severe hematoma, so an emergency tracheotomy was performed. It is important to monitor activated partial thromboplastin time (APTT) during the perioperative period, and administer fresh frozen plasma (FFP) to increase the level of factor XII, because of the high risk of postoperative bleeding complications.